Pesticides, Organic Contaminants, and Pathogens in Air - Seiber, James N.; Cahill, Thomas M. (Taylor & Francis, 2021)
"The air is an important but largely unrecognized source of contaminant fate in the environment, including transport of pesticides and contaminants to nontarget areas and exposures for people and wildlife. This book summarizes and places in perspective the potential transport, transformation, and health implications of pesticides and contaminants in air, including the air we breathe. It delves into the hypothesis that the atmosphere is the most significant environmental compartment affecting the overall transport and fate of many classes of environmental contaminants.